La casa senza amareni - Gian Piero Piretto (eSamizdat)
The article focuses on the lack of intérieur in Chekhov’s Cherry Orchard. The almost total absence of indications concerning the stage design underscores the spiritual emptiness of the house, a mansion that is no longer a home, where new characters (new social classes) arise in addition to the old landlords and take their places in organizing and altering the situation. Svetlana Boym’s considerations on “diasporic intimacy” help to emphasise the attitude of Ranevskaya towards the garden: she already lives elsewhere and her declarations of love for the orchard are nothing but empty, nostalgic words. She, and most of the other characters, long to leave and abandon the cherry orchard forever. The nursery is the only “furnished” room, according the Chekhov’s indications. The rest of the house is devoid of furniture, pictures, curtains, the “marks” that, according to Walter Benjamin, define the bourgeois intérieur of the 19th century. Old servant Firs, kitschy scenes, minor characters are the equivalent of the souvenirs that Soviet emigrants bring along when they leave the country. A short reflection on Stanislav Zhukovsky’s paintings of Russian mansion intérieur helps to demonstrate that The Cherry Orchard is not a drama, but a vaudeville.